1970
DOI: 10.2307/4593816
|View full text |Cite
|
Sign up to set email alerts
|

Gonorrheal Urethritis in Males Treated with a Single Oral Dose of Minocycline

Abstract: T HE EFFICACY of penicillin for the treatment of gonorrhea is waning. Increasing resistance of the gonococcus to penicillin during the past 20 years has forced escalation of the recommended dose from 160,000 units to 2,400,000 units for males and 4,800,000 units for females. Sulfonamides were widely used to treat gonorrhea at the end of the 1930's. Resistance of gonococci to sulfonamides today, however, is so great that by themselves they are no longer useful. We believe it is essential to try new drugs as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1971
1971
1980
1980

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 2 publications
0
3
1
Order By: Relevance
“…Our failure rates were much higher than those reported by Thatcher, Pazin and Domescik (1970) using minocycline in the treatment of gonococcal urethritis in men. Their failure rates in patients returning within 96 hours ranged from 8 per cent.…”
Section: Discussioncontrasting
confidence: 75%
“…Our failure rates were much higher than those reported by Thatcher, Pazin and Domescik (1970) using minocycline in the treatment of gonococcal urethritis in men. Their failure rates in patients returning within 96 hours ranged from 8 per cent.…”
Section: Discussioncontrasting
confidence: 75%
“…(Duncan and others, 1971) to 4-5 per cent. (Thatcher, Pazin, and Domescik, 1970). The present study compares the efficacy of two single-dose schedules in the treatment of uncomplicated gonorrhoea in men.…”
Section: Introductionmentioning
confidence: 96%
“…In view of the conflicting reports on the efficacy of minocycline for this purpose (Duncan, Glicksman, Knox, and Holder, 1971;Pariser and Marino, 1970;Thatcher, Pazin, and Domescik, 1970), a clinical trial was recently carried out at the Nottingham special treatment centre, which showed a cure rate of 94 1 per cent. in cases of uncomplicated gonorrhoea in males (Shahidullah, 1975).…”
mentioning
confidence: 99%